2016
DOI: 10.1186/s13068-016-0500-7
|View full text |Cite
|
Sign up to set email alerts
|

Model-based optimization and scale-up of multi-feed simultaneous saccharification and co-fermentation of steam pre-treated lignocellulose enables high gravity ethanol production

Abstract: BackgroundHigh content of water-insoluble solids (WIS) is required for simultaneous saccharification and co-fermentation (SSCF) operations to reach the high ethanol concentrations that meet the techno-economic requirements of industrial-scale production. The fundamental challenges of such processes are related to the high viscosity and inhibitor contents of the medium. Poor mass transfer and inhibition of the yeast lead to decreased ethanol yield, titre and productivity. In the present work, high-solid SSCF of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…The strain robustness was tested by cultivations in the liquid fraction (hydrolysate) of a wheat straw slurry, pre-treated by sulfuric acid-catalysed hydrolysis and steam explosion as described elsewhere [ 43 ] and containing inhibitors such as 3.8 g/l of acetic acid, 4.0 g/l of furfural and 1.4 g/l of 5-hydroxymethylfurfural (HMF); concentrations were determined by HPLC (see below). The pH of the hydrolysate was adjusted to 5.5 using concentrated NaOH, before being mixed with the above-mentioned medium and molasses as a source of sucrose [ 43 ] to achieve concentrations of hydrolysate ranging from 10 to 80% (v/v). Prior to microscale cultivations, B. coagulans MA-13 was grown into the stationary phase in LB medium at 55 °C and shaking speed of 180 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…The strain robustness was tested by cultivations in the liquid fraction (hydrolysate) of a wheat straw slurry, pre-treated by sulfuric acid-catalysed hydrolysis and steam explosion as described elsewhere [ 43 ] and containing inhibitors such as 3.8 g/l of acetic acid, 4.0 g/l of furfural and 1.4 g/l of 5-hydroxymethylfurfural (HMF); concentrations were determined by HPLC (see below). The pH of the hydrolysate was adjusted to 5.5 using concentrated NaOH, before being mixed with the above-mentioned medium and molasses as a source of sucrose [ 43 ] to achieve concentrations of hydrolysate ranging from 10 to 80% (v/v). Prior to microscale cultivations, B. coagulans MA-13 was grown into the stationary phase in LB medium at 55 °C and shaking speed of 180 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Only the overall process efficiency obtained in the present study (67%) can still be improved. In order to do that, efforts will Finally, a global analysis of the results obtained in the present study compared to the current literature on ethanol production by SSF in fed-batch mode using different biomass types at high solids content ( [17,31,33,[36][37][38][39] -Table 9) revealed that the strategy proposed here is very promising. As can be seen, Zhao et al [36] and Zhang et al [17] achieved the highest ethanol titers (80.0 and 84.7 g/L) using pre-treated sugarcane bagasse and corncob, respectively.…”
Section: Evaluation Of Fed-batch Strategiesmentioning
confidence: 98%
“…A macro-kinetic model was used to describe the bioprocess. The model was developed and validated by Wang et al (2016) to simulate batch and multi-feed SSF processes based on steam pretreated wheat straw at 5-15 filter paper units (FPU)·g −1 WIS and 0.02 g Cells ·g −1 WIS at maximally 13% water insoluble solids (WIS). Multi-feed SSF processes enable efficient mixing and high cell viabilities as solids and cells are added at discrete times with sufficient liquefaction in between.…”
Section: The Bioprocess Modelmentioning
confidence: 99%
“…Due to the solid additions and their subsequent hydrolysis, the cumulative WIS is higher than the 13% maximum operating WIS. In the case study the simulated multi-feed process conditions resembled the experimental conditions of a demo plant run at an enzyme activity of 9.3 FPU·g −1 WIS , a cell load of 0.02 g Cells ·g −1 WIS and a final cumulative WIS of 21.85%, with cell additions at 0, 12, 24, 48, and 72 h and solid additions at 0, 4, 12, 24, 48, and 72 h (Wang et al, 2016, Figure 6). Batch processes were simulated at identical relative cell and enzymatic activity loadings, but at 13% final WIS, all of which was added initially.…”
Section: The Bioprocess Modelmentioning
confidence: 99%
See 1 more Smart Citation